Post-Vaccination COVID-19 Transmission among Healthcare Workers in a Tertiary Level Hospital in Nepal - Shrestha, Battu Kumar; Dangol, Prati Badan; Bhusal, Surendra; Amatya, Ashish; Bhandari, Sandipa; Sapkota, Puspa Marasini (Nepalese Heart Journal, 2024)
Background and Aims: Frontline healthcare workers have faced an increased risk of contracting COVID-19 since the beginning of the pandemic. Nurses, in particular, faced a substantial risk compared to doctors, possibly due to their prolonged exposure to patients. Despite the vaccine coverage to healthcare workers before the second wave of the pandemic, breakthrough infection was unavoidable. Methods: This observational study was conducted at Shahid Gangalal National Heart Center, Kathmandu, Nepal, during the second wave of the COVID-19 pandemic. The study aimed to investigate COVID-19 infections among nursing staff, focusing on the number of infections, severity, the relationship between infections and time spent in the COVID ward, the comparison of infections among vaccinated and unvaccinated staff, and the effectiveness of infection control measures. Results: Among the 132 nursing staff, the overall positive rate after vaccination was 15.15%, with a breakthrough infection rate of 4.34%. Significant differences were observed in age and prior infection. However, no significant differences were observed among the type of family, education level, work experience, wards, total duty hours, level of PPE used, mask type, or mask reuse. Conclusion: Vaccines reduce the severity of infections but do not eliminate the risk, especially in high-exposure settings like healthcare facilities.